Tren dan Arah Penelitian Kompensasi dan Kepuasan Kerja (2018–2026): Bibliometric Analysis dan Systematic Literature Review - Nur Hasanah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Purpose – This study aims to systematically map and analyze research trends on compensation and job satisfaction from 2018 to 2026. Design/methodology/approach – This study adopts a bibliometric analysis combined with a systematic literature review (SLR) using data retrieved from the Scopus database. A total of 2,154 articles were initially identified, and 74 relevant articles were selected through the PRISMA 2020 framework. Data analysis was conducted using VOSviewer and Biblioshiny to examine publication trends, leading authors, institutional contributions, and keyword co-occurrence patterns. Findings – The findings reveal that research on compensation and job satisfaction has shown a generally increasing trend, despite some annual fluctuations. Core research themes are centered on job satisfaction, compensation, human resource management, and employee performance. Furthermore, emerging topics such as employee engagement, quality of work life, and emotional intelligence indicate a shift toward more contextual, employee-centered, and dynamic perspectives. However, the majority of existing studies still emphasize direct relationships between variables, with limited integration of contextual factors and evolving workplace dynamics. Practical implications – The results highlight the importance for organizations to implement a comprehensive total reward system that integrates both financial and non-financial compensation to enhance employee satisfaction and organizational outcomes. Originality/value – This study offers a comprehensive and up-to-date mapping of the literature, while also.